Local key management in opportunistic networks. (1st January 2012) - Shikfa, Abdullatif; Önen, Melek; Molva, Refik
Opportunistic networks are a new and specific type of mobile peer-to-peer networks where end-to-end connectivity cannot be assumed. These networks present compelling challenges, especially from a security perspective, as interactive protocols are infeasible in such environments. In this article, we focus on the problem of key management in the framework of content-based forwarding and opportunistic networks. After analysing this issue and identifying specific security threats such as Sybil attacks, we propose a specific key management scheme that enables the bootstrapping of local, topology-dependent security associations between a node and its neighbours along with the discovery of the neighbourhood topology, thanks to the use of pseudonym certificates and encapsulated signatures.